Optimized Pi Controller With Hybrid Sealion-Dragon Fly Algorithm For Grid-Tied PV System - Thangam, Thomas; Hemalatha, R.; Murali, M.; Manohar, V. Joshi (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The significance of solar energy in recent days has evidently increased with multiple benefits, because of which it is preferred in various applications of both rural and urban places. In this work, a SEPIC converter based grid tied PV system with a hybrid sea lion and dragonfly algorithm is employed. Generally the output of PV is obtained as low, to maximize the voltage level and to terminate the voltage fluctuations, the SEPIC converter is propounded in this work since it owns the capability of effectual voltage gain ratio. A closed loop control with PI controller has been implemented to maintain DC-link voltage as constant and a hybrid sea lion and dragonfly algorithm is introduced to tune parameters of PI controller. Then the obtained value is given to the grid through a VSI, which has assisted in converting the DC into AC. The PI controller has aided in generating the mandatory gating pulses of the VSI; the actual and reference powers are analogised, through which the grid synchronization and reactive power compensation have been magnificently achieved. The entire process has been validated through the MATLAB Simulink.